Administrative Control of Illegal Settlements on Former Cemetery Land in Surakarta - Pamungkasari, Dina Wahyu; Faried, Femmy Silaswati; Muhammad Aziz Zaelani (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
Illegal settlements in the former Bong Mojo cemetery area of Jebres, Surakarta, constitute a significant challenge to urban spatial planning. The construction of unauthorized buildings on land held under Right of Use (Hak Pakai) status reflects high housing demand, weak regulatory oversight, and insufficient enforcement of land law. This study examines the role of the Surakarta City Office of Housing, Settlement Areas, and Land Affairs in addressing the misuse of Hak Pakai land and identifies the institutional and practical obstacles encountered. Employing an empirical legal research design with a qualitative approach, data were collected through field observations, in-depth interviews, and document analysis. The findings indicate that the agency plays a strategic role in supervision, data management, law enforcement, and cross-sectoral coordination. However, implementation is constrained by limited institutional capacity, community resistance, complex land tenure arrangements, and low levels of regulatory compliance. High housing demand coupled with limited purchasing power further incentivizes illegal land use. This study underscores the need to strengthen spatial control policies, enhance inter-agency coordination, and expand access to affordable housing in order to promote orderly land use and ensure legal certainty in Surakarta.